Socio-Cultural Factors Influencing Uptake of Long-Acting Reversible Contraceptives among Reproductive Women in Kenya - Morris Karithi Njilu (Lakhomi Journal Scientific Journal of Culture, 2022)
Uptake of long-acting reversible contraceptives has been low among many women in Kenya. This has seen a surge in the number of unplanned pregnancies, which leads to continued poverty due to large sizes of families. This study therefore sought to establish the socio-cultural factors influencing the uptake of long-acting reversible contraceptives among women of reproductive age in Kenya. The study adopted descriptive cross sectional study design. The study was conducted in public hospitals in Kenya. The target population included the women of reproductive age of between 18 and 45 years. A sampling formula was used to identify the appropriate sample for the respondents. The 379 respondents identified were picked through simple random sampling. The data were collected using an interviewer-administered questionnaire. The collected data were analysed using descriptive statistics through SPSS version 26. The findings revealed that socio-cultural factors such as religious believe affected the uptake of long lasting reversible contraceptives among reproductive women in Kenya. The study concluded that through misconceived social cultural believes, the uptake of long lasting family planning methods/long-acting reversible contraceptives was minimal among reproductive women in Kenya. The study recommended the need for the government, the hospitals and other stakeholders to create awareness and education on the need for long-acting reversible contraceptives and other family planning methods among women. There is need for the communities to also embrace modern methods of family planning so as to stimulate their economic and social development.